2009
DOI: 10.1002/jctb.2172
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surfactants and biomass on the gas/liquid mass transfer in an aqueous‐silicone oil two‐phase partitioning bioreactor using Rhodococcus erythropolis T902.1 to remove VOCs from gaseous effluents

Abstract: BACKGROUND: The two-phase partitioning bioreactor (TPPB) has become a new strategy for waste gas treatment. However, the impact of biomass and surfactants on gas/liquid (G/L) mass transfer needs to be better evaluated because the effects on the mass transfer coefficient K L and the interfacial area a, respectively, remains misunderstood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…On the opposite, K L a decreases to a value of 0.0169 ± 0.0004 s -1 when 43 mL of antifoam agent is added to the broth (this quantity is equivalent to the one added during a cultivation run). This reduction of the global mass transfer efficiency is well described in the literature and can be related to greater bubble coalescence in the bulk liquid or adsorption of antifoam to the interfaces of bubbles and cells [14,21]. The following section involves the use of a DO-stat strategy to optimize the air flow rate and the foam formation intensity.…”
Section: Resultsmentioning
confidence: 97%
“…On the opposite, K L a decreases to a value of 0.0169 ± 0.0004 s -1 when 43 mL of antifoam agent is added to the broth (this quantity is equivalent to the one added during a cultivation run). This reduction of the global mass transfer efficiency is well described in the literature and can be related to greater bubble coalescence in the bulk liquid or adsorption of antifoam to the interfaces of bubbles and cells [14,21]. The following section involves the use of a DO-stat strategy to optimize the air flow rate and the foam formation intensity.…”
Section: Resultsmentioning
confidence: 97%
“…Theoretically, this situation is possible when the absorption of pollutant (IPB) largely exceeds the biological breakdown in the TPPB. However, previous studies12, 13 have shown that it was not conceivable in real conditions, essentially due to the biological limitations of the system. Consequently, for the concentrations currently encountered, the accumulation of the pollutant in the second phase does not disturb significantly the two‐phase system.…”
Section: Resultsmentioning
confidence: 97%
“…All the substrates and other chemicals were purchased from VWR International (Leuven, Belgium) or Aldrich (Bornem, Belgium). The strain was precultured and cultured, respectively, in 250 mL Erlemeyer shake flasks (150 rpm; 30 °C) and a bioreactor (as previously described13) containing M284, whose composition was (in g L −1 ): Na 2 HPO 4 , 17.7; NaH 2 PO 4 , 24.33 (buffer pH 7); NaCl, 4.68; KCl, 1.49; NH 4 Cl, 1.07; Na 2 SO 4 , 0.43; MgCl 2 ·6H 2 O, 0.20; Na 2 HPO 4 ·2H 2 O, 0.040; CaCl 2 ·2H 2 O, 0.030; Fe(III)NH 4 citrate, 0.0048; ZnSO 4 ·7H 2 O, 1.44 × 10 −4 ; MnCl 2 ·4H 2 O, 1 × 10 −4 ; H 3 BO 3 , 6.2 × 10 −5 ; CoCl 2 ·6H 2 O, 1.9 × 10 −4 ; CuCl 2 ·2H 2 O, 1.7 × 10 −5 ; NiCl 2 ·6H 2 O, 4 × 10 −5 ; Na 2 MoO 4 ·2H 2 O, 3.6 × 10 −5 . During the preculture, the Erlemeyer flasks were complemented with ethanol (1 g L −1 ) and IPB (1 g L −1 ) in order to gradually adapt the strain on the IPB.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other recent studies, silicone oil was selected against hexadecane, tetradecane and diethyl sebacate as the best non‐aqueous phase in a stirred‐tank bioreactor inoculated with Pseudomonas aeruginosa and in a biofilter inoculated with the fungus Fusarium solani 37, 38. More recently, Aldric and Thonart39 and Aldric et al 40 have successfully shown removal of a high inlet load of isopropyl benzene from gaseous effluents in a water–silicone oil TPPB system. In all these studies, silicone oil was the only non‐aqueous phase liquid that was biocompatible but not bioavailable, which further confirms the findings of the present study.…”
Section: Resultsmentioning
confidence: 99%